2019
DOI: 10.1017/jfm.2019.530
|View full text |Cite
|
Sign up to set email alerts
|

Fully dispersive models for moving loads on ice sheets

Abstract: The response of a floating elastic plate to the motion of a moving load is studied using a fully dispersive weakly nonlinear system of equations. The system allows for an accurate description of waves across the whole spectrum of wavelengths and also incorporates nonlinearity, forcing and damping. The flexural–gravity waves described by the system are time-dependent responses to a forcing with a described weight distribution, moving at a time-dependent velocity. The model is versatile enough to allow the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…Schulkes and Sneyd, 1988). Further studies have shown that the buildup of large enough deflections to break the ice may be limited by two-dimensional spreading (Nugroho et al, 1999), viscous effects (Wang et al, 2004), acceleration/deceleration through the critical speed (Miles and Sneyd, 2003) and/or non-linearities (Dinvay et al, 2019). Interestingly, a complementary field of study also exists that focuses on leveraging the resonant flexural waves produced by moving hovercraft to enhance their effectiveness as icebreakers (Hinchey and Colbourne, 1995;Kozin et al, 2017).…”
Section: A General Theory -Moving Loads On Floating Platesmentioning
confidence: 99%
“…Schulkes and Sneyd, 1988). Further studies have shown that the buildup of large enough deflections to break the ice may be limited by two-dimensional spreading (Nugroho et al, 1999), viscous effects (Wang et al, 2004), acceleration/deceleration through the critical speed (Miles and Sneyd, 2003) and/or non-linearities (Dinvay et al, 2019). Interestingly, a complementary field of study also exists that focuses on leveraging the resonant flexural waves produced by moving hovercraft to enhance their effectiveness as icebreakers (Hinchey and Colbourne, 1995;Kozin et al, 2017).…”
Section: A General Theory -Moving Loads On Floating Platesmentioning
confidence: 99%
“…Solution of such a problem cannot easily be obtained by analytical methods; however, contemporary numerical packages such as ANSYS CFD can be used. It is also worth mentioning that, as shown in [28], the influence of nonlinearity in the problem of moving loads on ice sheets becomes notable for rather big-amplitude FGWs. The influence of viscosity and nonlinearity in the general problem of ocean waves and ice interaction is reviewed in [1].…”
Section: Discussionmentioning
confidence: 93%
“…For a weakly nonlinear regime and two-dimensional problems, Parau & Dias (2002) derived a forced nonlinear Schrodinger equation for the envelope of ice sheet deflections caused by a load moving at a critical speed. Dinvay, Kalisch & Parau (2019) developed a fully dispersive weakly nonlinear model describing flexural-gravity waves in a floating elastic plate, excited by a moving load. For larger amplitudes, both forced and free steady waves were computed by Guyenne & Parau (2012) using direct numerical simulations with a boundary integral method.…”
Section: Numerical Resultsmentioning
confidence: 99%